2015
DOI: 10.4103/2229-5070.145581
|View full text |Cite
|
Sign up to set email alerts
|

Effect of enteric parasitic infection on serum trace elements and nutritional status in upper Egyptian children

Abstract: Introduction:Enteric parasitic infections still the cause of major health problems among Egyptian children as they have great morbid effect on their physical and cognitive development. Malnutrition makes children more prone to micronutrient deficiency and subsequently more vulnerable to parasitic infection. The present study aimed to identify the effect of intestinal parasitism on micronutrient serum level and children nutritional status.Materials and Methods:A case control study was carried out on children fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 29 publications
5
24
0
2
Order By: Relevance
“…Appropriate nutrition methodologies, with food protection and modification, along with community health actions directed at parasitic control and parental care, must be established. Consistent with these findings, [24] in their study of upper Egyptian children reported that 63% of infected children and 41% of non-infected children had malnutrition.…”
Section: Discussionsupporting
confidence: 75%
“…Appropriate nutrition methodologies, with food protection and modification, along with community health actions directed at parasitic control and parental care, must be established. Consistent with these findings, [24] in their study of upper Egyptian children reported that 63% of infected children and 41% of non-infected children had malnutrition.…”
Section: Discussionsupporting
confidence: 75%
“…A close relationship between IPIs and malnutrition has been reported especially among chronically infected children. 32 Intestinal parasitism may cause or aggravate malnutrition by their intense effects on intestinal digestion and absorption. Adult helminth worms residing in the small intestine interfere with their host nutrition and can induce damage to the intestinal mucosa that may reduce a person's ability to extract and absorb nutrient from food.…”
Section: Intestinal Parasitic Infections-induced Malnutritionmentioning
confidence: 99%
“…35 Alterations in the serum concentrations of these elements are commonly found in patients with IPIs, mainly G. lamblia and Cryptosporidium. 32 Their deficiency leads to suppressed immunity predisposing to infections which sequentially exacerbate the nutritional status. 36 Also, their decline stimulates the oxidative stress which is implicated in the pathogenesis of several diseases, including cardiovascular diseases, cancer, and in some parasitic infections.…”
Section: Intestinal Parasitic Infections-induced Malnutritionmentioning
confidence: 99%
“…Parasitic infections have been reported in about 25% of the world's population. These infections are more prevalent in developing countries, especially in rural areas of tropical and subtropical regions (1,2). In Egypt, parasitic diseases represent a serious public health problem in both immunocompetent and immunocompromised patients with clinical and economic impacts.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of parasitic infections among children is high, with levels reaching up to 50%. This high prevalence is mainly due to overcrowding and poor hygiene patterns that significantly contributed to the spread of parasitic infections (1)(2)(3).…”
Section: Introductionmentioning
confidence: 99%